SY 07-2 SHOULD DIABETES MELLITUS REMAIN A COMPELLING INDICATION FOR USE OF RENIN ANGIOTENSIN SYSTEM BLOCKERS?. (September 2016) - Messerli, Franz
Abstract : OBJECTIVE: To evaluate the outcomes with use of renin angiotensin system (RAS) blockers compared with other antihypertensive agents in people with diabetes. DESIGN: Meta-analysis. DATA SOURCES AND STUDY SELECTION: PubMed, Embase, and the Cochrane central register of controlled trials databases for randomized trials of RAS blockers versus other antihypertensive agents in people with diabetes mellitus. Outcomes were death, cardiovascular death, myocardial infarction, angina, stroke, heart failure, revascularization, and end stage renal disease. RESULTS: The search yielded 19 randomized controlled trials that enrolled 25, 414 participants with diabetes for a total of 95, 910 patient years of follow-up. When compared with other antihypertensive agents, RAS blockers were associated with a similar risk of death (relative risk 0.99, 95% confidence interval 0.93 to 1.05), cardiovascular death (1.02, 0.83 to 1.24), myocardial infarction (0.87, 0.64 to 1.18), angina pectoris (0.80, 0.58 to 1.11), stroke (1.04, 0.92 to 1.17), heart failure (0.90, 0.76 to 1.07), and revascularization (0.97, 0.77 to 1.22). There was also no difference in the hard renal outcome of end stage renal disease (0.99, 0.78 to 1.28) (power of 94% to show a 23% reduction in end stage renal disease). CONCLUSIONS: In people with diabetes, RAS blockers are not superior to other antihypertensive drug classes such as thiazides, calcium channel blockers, and β blockers at reducing the risk of hard cardiovascular and renal endpoints. These findings support the recommendations of the guidelines of the European Society of Cardiology/European Society of Hypertension and eighth Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure to also use other antihypertensive agents in people with diabetes but without kidney disease.